PENGARUH PENDEKATAN PENGAYAAN GERAK DASAR MELALUI AKTIVITAS BERMAIN TERHADAP KEBUGARAN JASMANI, DAN MOTOR EDUCABILITY, DALAM KAITANNYA DENGAN PERBEDAAN LINGKUNGAN SOSIAL, BUDAYA DAN GEOGRAFIS ANTARA DESA DAN KOTA - Kahri, Ma'ruful (2012)
The problem that faced in physical education at the present time is the happening of change of culture's values. It was indicated by changing of physically active into less bodily movement life style. This physical fondling is triggered by multifarious amenity of the usage of communication technology and transportation that caused the children as the human being (homo luden) tend to decrease and even eliminate physical activity in all daily life. This could be happened by low of their physical fitness, and motor educability of the child. An experiment method was applied, with the design of pre-test and post-test design. Data that gathered by Indonesian Fitness Test Standard and IOWA Brace Test were analyzed by using statistical technique of MANOVA. The result such as follows: First, there is a significant influence of enrichment model basic motion pass approach between physical fitness and motor educability of the children who play game activities and its children who were taught by model direct instruction. Second, there is a significant influence of social environment context, culture and geographical within the students of village and city school. Third, there is a significant interaction between enrichment of basic motion pass approach that was taught game activities and its model direct instruction with geographical environment context (within physical fitness and motor educability of the village and city school students). Conclusion: The Model of enrichment of basic motion pass approach which were applied by game activity and model direct instruction are jointly related to environment context within the physical fitness and motor educability of the village and city school. Key word: Enrichment Basic motion Approach, Direct Instruction Approach, Environment Context (countryside and city), Physical fitness, and Motor Educability.